Konsep Negara Hukum dan Demokrasi Serta Kaitannya dengan Hak Asasi Manusia - Selma Nabila Azzahra; Imam Hakiki (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to answer the following questions: First, what are the concepts of the rule of law and democracy, and how are they related? Second, what is the concept of human rights and how does it relate to the rule of law and democracy in Indonesia? The method used in this study is normative legal research, focusing on the study of legislation and scientific literature on the rule of law, democracy, and human rights. The approaches used include a legislative approach to examine the provisions of the 1945 Constitution of the Republic of Indonesia and related regulations; a conceptual approach to examine the theory of the rule of law, the theory of democracy, and the theory of human rights; and a historical approach to trace the development of these three concepts in the Indonesian context. The research data was obtained from primary and secondary legal materials. The results of the study show that the concepts of the rule of law and democracy are two interrelated and inseparable principles. Both in the traditions of the rechstaat and the rule of law, respect for human rights is placed as a key pillar, which is now understood more broadly to include issues of freedom, social justice, and protection from arbitrariness. The relationship between human rights, democracy, and the rule of law affirms that the law must be the highest authority, with the constitution as its highest foundation. The supremacy of law is an important element in the practice of democracy because the constitution functions as a social contract that regulates power and guarantees the protection of human rights.